2006
DOI: 10.1097/01.scs.0000246728.23483.ce
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Oral Tumors in Iran

Abstract: This study analyzed characteristics of oral cancer patients from Tehran, Iran, and their tumors. Data came from the patient records of 30 major hospitals in Tehran. Patients (n = 1042), diagnosed with invasive oral cancer in 1993-2003, were classified by primary tumor site according to ICD-10 (C00-C10). Data were analyzed separately for lip, oral cavity and salivary gland tumors. Statistical evaluation included chi and t-test. Of all cases, 59% were male. Age for all cases ranged from 6-103 years, mean age was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
17
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 16 publications
6
17
2
Order By: Relevance
“…The finding of this study that OSCC constitutes 41% of all oral malignancies was in sharp contrast to most previous studies which showed that OSCC accounts for 70-95% of all oral malignancies (3,11-13). However, our finding was consistent with that of Ajayi et al (8) who reported that OSCC accounts for 44% of all oral malignancies.…”
Section: Discussioncontrasting
confidence: 99%
“…The finding of this study that OSCC constitutes 41% of all oral malignancies was in sharp contrast to most previous studies which showed that OSCC accounts for 70-95% of all oral malignancies (3,11-13). However, our finding was consistent with that of Ajayi et al (8) who reported that OSCC accounts for 44% of all oral malignancies.…”
Section: Discussioncontrasting
confidence: 99%
“…Last but not least, illiteracy, poverty and chronic debilitating diseases are prevalent in Yemen. Among populations with somewhat similar circumstances like Nigerians (22), Thais (6), Brazilians (15) and Iranians (23), high proportion of advanced oral cancer has been reported (100%, 73%, 65% and 50% respectively). On the other side, high proportion of oral cancer cases in the developed world are diagnosed at early stages (12,24).…”
Section: Discussionmentioning
confidence: 99%
“…Due to limited access to diagnostic and treatment services in low-income communities and to the high cost of services, people present with advanced stage lip and oral cavity cancer at the time of diagnosis. All the aforementioned are among the important reasons for the low 5-year survival of patients as well as the higher mortality rates in developing countries (Funk et al, 2002;Global Burden of Disease Cancer, 2015;Patel et al, 2012;Sargeran et al, 2008). McDonald et al reported in their study that there was lower survival of head and neck cancers, including oral cavity cancer, in people of low socioeconomic statuses (McDonald et al, 2014).…”
Section: Discussionmentioning
confidence: 99%